Patrimoine industriel et identité territoriale dans les Ardennes - Marcel Bazin (Territoire en Mouvement)
The notion of industrial heritage has compelled recognition rather late in France. It raises the interest of geographers and planners as well as of economists in the framework of an interdisciplinary dialogue. In fact, these disciplines are concerned by the genesis of this heritage through decline or reconversion of industries, showing various temporalities and geographical distributions, by the identification and appropriation processes leading to territorial affirmation, and by the perspectives and problems of conservation and valorization of this heritage.The case study of French Ardennes has been chosen to illustrate these issues of industrial heritage. The valley of Meuse river between Mouzon and Givet constitutes an “industrial arc” taking its strong personality from the predominance of metal works. This industrial region was severely struck by crisis and desindustrialization trend after 1975, in spite of some diversification, leaving a considerable amount of abandoned buildings and wasteland. The visibility of this heritage is high, thanks to its spatial concentration along the valleys. The patrimonialization process has occurred through social and cognitive appropriation leading to a strong multifaceted (and sometimes controverted) identity, including characteristic landscapes, technical know-how and socio-political memory of the Red Valley. How far can the valorization of this industrial heritage contribute to local development ?